2021
DOI: 10.1038/s41598-021-98249-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors shaping public responses to COVID-19 digital contact tracing technologies in Germany

Abstract: The COVID-19 pandemic has seen one of the first large-scale uses of digital contact tracing to track a chain of infection and contain the spread of a virus. The new technology has posed challenges both for governments aiming at high and effective uptake and for citizens weighing its benefits (e.g., protecting others’ health) against the potential risks (e.g., loss of data privacy). Our cross-sectional survey with repeated measures across four samples in Germany ($$N = 4357$$ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 41 publications
(47 reference statements)
1
12
0
Order By: Relevance
“…Considering the lower motivation that participants placed on CTA Immuni compared with the vaccine, data showed that high trust in politics and science was the main determinant of the intention to download the CTA Immuni. This finding is in line with literature on CTAs, as trust in the state appeared to be, among others, a factor positively associated with the willingness to download a CTA, trust that refers to the government’s ability to ensure people’s privacy and manage access to data 17 , 21 , 49 . In addition, considering the intention to get vaccinated, previous studies showed that vaccine acceptance is positively affected by trust in the healthcare system, government, and public health researchers 32 .…”
Section: Discussionsupporting
confidence: 89%
“…Considering the lower motivation that participants placed on CTA Immuni compared with the vaccine, data showed that high trust in politics and science was the main determinant of the intention to download the CTA Immuni. This finding is in line with literature on CTAs, as trust in the state appeared to be, among others, a factor positively associated with the willingness to download a CTA, trust that refers to the government’s ability to ensure people’s privacy and manage access to data 17 , 21 , 49 . In addition, considering the intention to get vaccinated, previous studies showed that vaccine acceptance is positively affected by trust in the healthcare system, government, and public health researchers 32 .…”
Section: Discussionsupporting
confidence: 89%
“…Each participant provided informed consent and demographic information before using a Likert scale to report on their perceptions and impact of the COVID-19 pandemic. Participants then read one of three hypothetical scenarios describing a different type of mobile phone COVID-19 contact-tracing system—telecommunication tracking, a government app, or the Apple/Google exposure notification system—that would alert the user if they had contact with an infected individual, before completing a comprehension check and answering questions about these scenarios (for methods and results on these items by country, see [ 23 , 25 - 27 ]; note that these studies do not model immunity passport items). Finally, participants read a description of immunity passports before responding to items examining their attitudes toward immunity passports and their neoliberal worldviews.…”
Section: Methodsmentioning
confidence: 99%
“…A modelling study showed that this app averted about one case per index case willing to send the notification to their contacts [ 39 ]. The percentage of the population who downloaded tracing apps was also high in countries such as Germany, Switzerland, and Finland (ie, 32%-45%), but much lower in Spain, Italy, and France (ie, 15%-19%) [ 40 ]. This high level of adoption in some countries could be driven by the fact that the National Health Service app and the German app are among several apps that combine the tracing function with other features such as local area risk indicators and a link for booking a test, or by differences in promotion efforts.…”
Section: Discussionmentioning
confidence: 99%